AFTER LYNN WHITE: RELIGIOUS ETHICS AND ENVIRONMENTAL PROBLEMS - Jenkins, Willis (Journal of religious ethics, 2009)
The fields of environmental ethics and of religion and ecology have been shaped by Lynn White Jr.'s thesis that the roots of ecological crisis lie in religious cosmology. Independent critical movements in both fields, however, now question this methodological legacy and argue for alternative ways of inquiry. For religious ethics, the twin controversies cast doubt on prevailing ways of connecting environmental problems to religious deliberations because the criticisms raise questions about what counts as an environmental problem, how religious traditions change, and whether ethicists should approach problems and traditions with reformist commitments. This article examines the critiques of White's legacy and presents a pluralist alternative that focuses religious ethics on the contextual strategies produced by moral communities as they confront environmental problems.